PRobust: a percolation-based robustness optimization model for underwater acoustic sensor networks - Zhang, Zhaowei; Liu, Chunfeng; Qu, Wenyu; Zhao, Zhao; Guo, Weisi (Institute of Electrical and Electronics Engineers (IEEE), 2025)
In Underwater Acoustic Sensor Networks (UASNs), the robustness of network is greatly affected by complex marine environments when implementing multi-hop data transmission. Factors such as the underwater acoustic channel and dynamic topological changes induced by multi-layered oceanic vortices exacerbate this influence. However, there is currently a research gap in the specific area of robustness optimization for UASNs. Existing studies on robustness optimization are unsuitable for UASNs as they neglect the considerations of the marine environment and node characteristics (e.g., residual energy). In this work, we propose PRobust, a percolation-based robustness optimization model for UASNs. PRobust consists of two distinct phases: percolation modeling and bottleneck optimization. In the percolation modeling phase, we incorporate both node and edge features, considering the physical and topological properties, and introduce a novel approach for calculating link quality. In the bottleneck optimization phase, we devise a graph theory-based method to identify bottlenecks, leveraging the flow information recorded by nodes to improve the accuracy of bottleneck discovery. Moreover, we integrated time slots and a current movement model into the proposed model, allowing its applicability to dynamically changing UASNs. Extensive simulation results indicate that, compared to existing methods, PRobust significantly enhances network robustness and performance with the same overhead after bottleneck optimization.
Keywords: 4605 Data Management and Data Science; 4606 Distributed Computing and Systems Software; 46 Information and Computing Sciences; 14 Life Below Water; Networking & Telecommunications; 4006 Communications engineering; 4604 Cybersecurity and privacy; Underwater Acoustic Sensor Networks; Robustness Optimization; Percolation; Current Movement; Data Transmission; Network Traffic